Women Writers and Familial Discourse in the English Renaissance - Wynne-Davies, M. author. aut Link
VIII, 209 p.
Keywords: This book explores the development of familial discourse within a chronological frame, commencing with the More family and concluding with the Cavendish group. It explores the way in which the support of family groups enabled women to participate in literary production, whilst closeting them within a form of writing that encompassed style or theme.